PEMANFAATAN PETILASAN MACAN PUTIH SEBAGAI SUMBER BELAJAR SEJARAH LOKAL BAGI GENERASI MUDA - Tian Fitriara Huda (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2016)
This study aims to (1) determine the strategy that is used in the White Tiger Petilasan utilization as a source of learning local history to the younger generation, (2) know how learning methods are applied in the functioning Petilasan White Tiger as a source of learning local history. This study is a qualitative research, with research steps such as (1) the determination of the study design, (2) determining the location of the research, (3) determination of informants, (4) data collection, (5) the validity of the data that consists of triangulation data and triangulation methods, (6) the data analysis. The results showed that three schools located near Petilasan, SMAN 1 Rogojampi, SMA PGRI Rogojampi and SD Negeri 1 Macan Putih, Macan Putih Petilasan utilize as a source of learning local history. How utilization is to use contextual learning strategies (contextually Teaching Learning) with several learning methods. Teachers SMAN 1 Rogojampi, SMA PGRI Rogojampi using the browsing environment and purely historical study method. While teachers SD Negeri 1 Macan Putih using the method of socialization in Petilasan use this as a learning resource.